2000
DOI: 10.1007/s001130050612
|View full text |Cite
|
Sign up to set email alerts
|

Die Balser-Platte mit Bandnaht

Abstract: Between June 1990 and December 1997 116 patients with complete dislocation of the acromio-clavicular joint were treated operatively. According to the classification of Tossy and Rockwood all patients had type Tossy III or Rockwood III, IV and V of lesion. The retrospective part of the study from June 1990 to August 1994 represents 48 patients treated in 31 cases with wire-cerclage, in 14 cases with PDS-cerclage and in 3 cases with a combination of Kirschner wires and PDS. In a second group between September 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The use of ultrasound diagnosis of fractures has been assessed in several studies with various results [4,[11][12][13][14][15][16][17]. Most studies included heterogeneous pathologies in a wide variety of locations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound diagnosis of fractures has been assessed in several studies with various results [4,[11][12][13][14][15][16][17]. Most studies included heterogeneous pathologies in a wide variety of locations.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies used tension bands and Kirschner wires applied through the acromioclavicular joint2, 30 and extraarticular Bosworth screws to maintain reduction 3, 31. However, loosening or breakage of the implants was reported after surgery because of stress concentration and non-dynamic fixation 2, 32.…”
Section: Discussionmentioning
confidence: 99%
“…However, loosening or breakage of the implants was reported after surgery because of stress concentration and non-dynamic fixation 2, 32. The clavicular hook plate works by generating a leverage force through the proximal end of the plate to the acromion as a dynamic fixation and can maintain clavicle position and CC distance to achieve satisfying results 30, 33, 34. One study showed that hook plate fixation is the closest method to the normal biomechanics of the AC joint 35 …”
Section: Discussionmentioning
confidence: 99%
“…LCDC-Platte komplikationslos bewährt. Gute Erfahrungen mit der Balserplatte [1] als temporäre extraartikuläre Fixation bei der Schultereckgelenksprengung[9] haben uns veranlasst, diese Technik bei den lateralen Frakturen zunehmend einzusetzen. Je nach Fraktur-Typ in der Klassifikation nach Jäger und Breitner[15] wurden die korakoklavikulären Bänder zusätzlich durch eine Naht adaptiert.…”
unclassified